Blood glucose and sepsis score on sepsis patients requiring insulin therapy - Mohamad Suhaimi, Fatanah; Jamaludin, Ummu Kulthum; Abdul Razak, Normy Norfiza; Pretty, Christopher G.; Md Ralib, Azrina; Mat Nor, Mohd Basri; Dzaharudin, Fatimah (Springer Verlag, 2018)
Early treatment of sepsis is crucial in improving the patient condition and reduces mortality. The lack of information and methods to diagnose sepsis at an early stage is a significant barrier to early treatment. Treatment is normally based on clinical judgment since blood cultures are negative in the majority of sepsis or septic shock cases as reported in several studies. Even with blood cultures result, a delay in diagnosis may happen while waiting for the results. Therefore, clinical guidelines are still required to provide guidance for the clinician caring for a patient with severe sepsis or septic shock. In this study, a validated glucose-insulin model is used to capture patient-specific insulin sensitivity profile. The validated model is incorporated with a sepsis system to create a glucose-insulin model that describe sepsis occurrence. The relationship between insulin sensitivity, blood glucose and sepsis score is investigated using a retrospective data of 8 patients admitted in the Tengku Ampuan Afzan Hospital, Kuantan. Results indicate that there was a significant relationship between blood glucose level and sepsis score (p < 0.001), and insulin sensitivity with a sepsis score (p < 0.001). Additionally, blood glucose level was higher in a severe sepsis group compared to the non-sepsis group. Whereas, insulin sensitivity is lower in a severe sepsis group. Insulin sensitivity profile can be incorporated with the sepsis system for monitoring sepsis patients requiring insulin therapy as seen in this study. Thus, the sepsis glucose-insulin model can potentially be used as an indicator or tools for sepsis diagnosis.